Practical aspects of using of parallel computing in genetic algorithm - V. V. Frolov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Practical implementation methods for parallel computations in the genetic algorithm for discrete optimization, using the example of calculating dimensional chains are considered. An approach for determining the boundary dimensions of population on the basis of probability calculating for independent random events is proposed.